Studying electron transfer through alkanethiol self-assembled monolayers on a hanging mercury drop electrode using potentiometric measurements - Cohen-Atiya, Meirav; Mandler, Daniel (Phys Chem Chem PhysPhysical chemistry chemical physics : PCCP, 2006)
A new approach based on measuring the change of the open-circuit potential (OCP) of a hanging mercury drop electrode (HMDE), modified with alkanethiols of different chain length conducted in a solution containing a mixture of Ru(NH3)6(2+) and Ru(NH3)6(3+) is used for studying electron transfer across the monolayer. Following the time dependence of the OCP allowed the extraction of the kinetic parameters, such as the charge transfer resistance (R(ct)) and the electron transfer rate constant (k(et)), for different alkanethiol monolayers. An electron tunneling coefficient, beta, of 0.9 A(-1) was calculated for the monolayers on Hg.[on SciFinder (R)]
MEDLINE AN 2006572179(Journal; Article; (JOURNAL ARTICLE); (RESEARCH SUPPORT, NON-U.S. GOV’T))